Effects of Branched-Chain Amino Acid Supplementation on Spontaneous Seizures and Neuronal Viability in a Model of Mesial Temporal Lobe Epilepsy. Issue 2 (April 2019) - Gruenbaum, Shaun E.; Dhaher, Roni; Rapuano, Amedeo; Zaveri, Hitten P.; Tang, Amber; de Lanerolle, Nihal; Eid, Tore
Abstract : Background: The essential branched-chain amino acids (BCAAs) leucine, isoleucine, and valine have recently emerged as a potential novel treatment for medically refractory epilepsy. Blood-derived BCAAs can readily enter the brain, where they contribute to glutamate biosynthesis and may either suppress or trigger acute seizures. However, the effects of BCAAs on chronic (ie, spontaneous recurrent) seizures and epilepsy-associated neuron loss are incompletely understood. Materials and Methods: Sixteen rats with mesial temporal lobe epilepsy were randomized into 2 groups that could drink, ad libitum, either a 4% solution of BCAAs in water (n=8) or pure water (n=8). The frequency and relative percent of convulsive and nonconvulsive spontaneous seizures were monitored for a period of 21 days, and the brains were then harvested for immunohistochemical analysis. Results: Although the frequency of convulsive and nonconvulsive spontaneous recurrent seizures over a 3-week drinking/monitoring period were not different between the groups, there were differences in the relative percent of convulsive seizures in the first and third week of treatment. Moreover, the BCAA-treated rats had over 25% fewer neurons in the dentate hilus of the hippocampus compared with water-treated controls. Conclusions: Acute BCAA supplementation reduces seizure propagation, whereas chronic oral supplementation with BCAAs worsens seizure propagation and causes neuron loss in rodents with mesial temporal lobe epilepsy. These findings raise the question of whether such supplementation has a similar effect in humans.